2017
DOI: 10.1371/journal.pone.0182385
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of biological systems using SPICE language

Abstract: The article deals with BB-SPICE (SPICE for Biochemical and Biological Systems), an extension of the famous Simulation Program with Integrated Circuit Emphasis (SPICE). BB-SPICE environment is composed of three modules: a new textual and compact description formalism for biological systems, a converter that handles this description and generates the SPICE netlist of the equivalent electronic circuit and NGSPICE which is an open-source SPICE simulator. In addition, the environment provides back and forth interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 71 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…He also observed that when he inoculated laboratory animals with lethal doses of typhoid bacilli together with Penicillium glaucum, the animals did not contract typhoid. 8 Unfortunately, Duchesne's army service after getting his degree prevented him from doing any further research. Duchesne died of tuberculosis, a disease now treated with antibiotics.…”
Section: Introduction A) Historymentioning
confidence: 99%
“…He also observed that when he inoculated laboratory animals with lethal doses of typhoid bacilli together with Penicillium glaucum, the animals did not contract typhoid. 8 Unfortunately, Duchesne's army service after getting his degree prevented him from doing any further research. Duchesne died of tuberculosis, a disease now treated with antibiotics.…”
Section: Introduction A) Historymentioning
confidence: 99%
“…Finally, the reaction model, also written in SPICE via the BB-SPICE environment [12], are added for each node in areas where reactions occur. Third-party models written in Verilog-A or SPICE, such as the model of a sensor, can also be connected to the lattice to simulate an output electrical signal that depends on the local concentration.…”
Section: A Overview Of the Modelmentioning
confidence: 99%
“…Finally, local reactions can be added to the lattice. Biochemical reactions are modeled by SPICE sub-circuits that can be automatically generated from a biochemical description with BB-SPICE [12]. The model has one terminal per involved chemical species.…”
Section: ) Chemical Reactionmentioning
confidence: 99%
“…2. Spice: An international standard that is continuously being developed for software processes, this standard contains stages which are preparation, data collection, compilation and analysis (Dorling, 1993;Madec et al, 2017;Tupe et al, 2009). 3.…”
Section: Legal Regulationsmentioning
confidence: 99%